Alliance of Bioversity International/CIAT collaboration with the Adaptation Consortium (ADA): Evaluating the conflict sensitivity of the County Climate Change Fund (CCCF) mechanism - Schapendonk, Frans; Medina, Leonardo (2024)
The interface of climate change, conflict, and peace is fraught with complexity and place-specific contingency. Climate impacts may, for instance, increase the risk of competition and conflict (primarily indirectly) by undermining natural resource availability and access, but may also elicit more cooperative community responses in the face of shared risks and threats. Building on this awareness and using its newly developed Conflict Sensitive Adaptation Governance (CSAG) framework, CGIAR’s Alliance of Bioversity International/CIAT have partnered with the Adaptation (Ada) Consortium in Kenya to analyse and evaluate Kenya’s County Climate Change Fund (CCCF) mechanism, a multi-level climate finance instrument designed on the basis of locally led adaptation (LLA) principles and which forms a central pillar of Kenya’s National Climate Change Action Plan III (2023-2027).